PENGARUH PEMBELAJARAN TERBIMBING (GUIDED TEACHING) TERHADAP PENINGKATAN KEMANDIRIAN BELAJAR MAHASISWA - Kristin, Firosalia (Jurnal Pendidikan Ilmu Sosial, 2018)
The objective of this research was to examine the influence of guided teaching on students’ independent learning. This research was an action research / preexperimental design research in RS15A of second year students in Bachelor degree of Primary Education in Satya Wacana Christian University. The instrument to test the student’s independent learning was tested in RS15B class. The instrument was qualified to be used in the research and it was used for pretest and posttest. The enhancement of students’ independent learning was shown by a significant difference between posttests and pretest. The inferential data analisys were performed using independent sample t-tests. The results showed that there were significant differences between pretest and posttest. Moreover, Guided Teaching were able to increase students’ independent learning by 59%.